Towards indicative baseline and decarbonization pathways for embodied life cycle GHG emissions of buildings across Europe. Issue 1 (1st September 2022) - Röck, M; Allacker, K; Auinger, M; Balouktsi, M; Birgisdottir, H; Fields, M; Frischknecht, R; Habert, G; Hvid Horup Sørensen, L; Kuittinen, M; Le Den, X; Lynge, K; et al.
Abstract: Buildings' construction and operation are major contributors to global greenhouse gas (GHG) emissions, and the substantial reduction of GHG emissions across their full life cycle is required to enable meeting international climate targets. For effective climate change mitigation - as recent studies have shown - a special focus has to be put on lowering embodied GHG emissions, i.e., emissions related to construction production manufacturing and construction processes, maintenance and replacement as well as end-of-life processing. As the importance of reducing embodied GHG emissions rises, so does the need for understanding both the baseline and pathways for reduction across the full life cycle of buildings. In this paper, we offer insights into the data-driven analysis of embodied GHG emissions across the whole life cycle of buildings from recent studies. Our investigation builds on the data collection, processing and harmonisation of around 1.000 building LCA case studies. We offer an integrated perspective on GHG emissions across the life cycle of buildings, considering historical trends, current baselines and indicative reduction pathways for embodied GHG emissions in different countries across Europe. This serves to inform our current 'decade of action' and the transformation to a regenerative built environment by 2050.